Effects of peripheral blood neutrophil/lymphocyte ratio levels and their changes on the prognosis of patients with early cervical cancer - Du, Jun-Qiang; Zhang, Fan; Wang, Chao-Qun; Zhu, Ju-Fan; Xu, Li-Xia; Yang, Yi-Heng; Han, Meng-Fei; Hu, Yan (Frontiers in Oncology, 2023)
Although some studies have reported on the levels and clinical significance of peripheral blood neutrophil/lymphocyte ratio (NLR) in cervical cancer, the role of NLR levels and their changes preoperatively and postoperatively in early cervical cancer remain unclear. Our analyses explored the preoperative and postoperative NLR in 203 patients with stage I-IIA cervical cancer and evaluated the relationship between NLR changes, clinicopathological characteristics, and patient prognosis. The cut-off preoperative and postoperative NLR values were determined using receiver operating characteristic curve analysis. Preoperative NLR correlated with age, menopausal status, tumor size, and vascular infiltration, whereas postoperative NLR correlated with tumor differentiation. Patients with cervical cancer with a high preoperative NLR had significantly shorter overall survival (OS) and progression-free survival (PFS) than other patients, whereas PFS was significantly lower in the high postoperative NLR group. When comparing postoperative and preoperative NLR values, we observed a significantly higher rate of increase in postmenopausal patients and those without vascular infiltration than that among premenopausal patients and those with vascular infiltration. However, no clear difference in prognosis was observed between the groups with increased and decreased NLR. Therefore, a high peripheral blood NLR may predict a poor prognosis in patients with early cervical cancer. The effect of NLR changes on the prognosis of patients with cervical cancer requires further verification in multicenter studies.